Sustainable Water Resource Management in Afghanistan: Challenges and Solutions - Azimi, Rafiullah; Dehghani, Hamid (Journal of Natural Sciences – Kabul University, 2026)
Water, as a shared human resource, plays a fundamental role in achieving sustainable development, and its proper preservation and transfer to future generations is considered a strategic necessity. In Afghanistan, increased consumption, degradation of water resources, and weak management threaten development sustainability, with the impacts affecting low-income populations the most. This article is a descriptive-analytical review study based on library research and the examination of reputable scientific sources on Afghanistan’s conditions. The data, after refinement, were analyzed to identify challenges and strategies for sustainable water resources management. Findings indicate that recurrent droughts, rapid population growth, climate change, water pollution, and inadequate management are among the main challenges. Conversely, promoting a culture of conservation, optimal water resource management, development of water supply infrastructure, increasing water productivity in agriculture, protecting water resources, and strengthening regional and international cooperation are considered key strategies for sustainable water management.